RANCANG BANGUN SISTEM INFORMASI PENGAJUAN KREDIT BERBASIS WEB PT. BUANA SEJAHTERA MULTIDANA - Budi Sudradjat (Jurnal Ilmiah Informatika, 2017)
Credit application system is a system that is still rare and potentially good for any people who use the internet. Credit application system is an easy and practical way to apply for loans include credit applications until the approval stage. In general, credit application system is still based on manual which led to a long process, loss of data, to prospective customers who fled for being too slow. The system is very helpful that the authors make the credit application process becomes more quickly, efficiently and accurately. With a little easier new customers and existing customers with the rotation system will accelerate the economy in the company of PT. Buana Sejahtera Multidana which will impact also on the company's profits.